Impact of Sociocultural Mediation on Exhumation Timeline and DNA Yield in Medicolegal Investigations: A Retrospective Survival Analysis from Rural South Sumatra - Dedi Kusmanto; Hendri Safitri; Firzan Dahlan; Fachrudin Sani (Sriwijaya Journal of Forensic and Medicolegal, 2026)
Introduction: Forensic medicolegal investigations in rural Indonesia are frequently conditioned by sociocultural practices that govern community consent for exhumation. Four distinct mediation pathways — direct family authorization, elder-mediated, religious leader-mediated, and multiple-mediator — are commonly observed in South Sumatran casework, yet their quantitative impact on exhumation timeline and downstream DNA extraction success has not been formally characterized. Methods: We conducted a retrospective cohort study of 120 consecutive medicolegal exhumation cases at Hospital X, South Sumatra, January 2018 – December 2022. Mediation type was classified from case file records. Time-to-exhumation was analysed by Kaplan-Meier survival estimation and log-rank testing; adjusted hazard ratios were estimated by Cox proportional hazards regression. Binary DNA extraction success (≥1 ng/µL by real-time PCR) was modelled by multivariable logistic regression with 1000-iteration bootstrap confidence intervals. Results: The four mediation groups (Direct n=35; Elder n=42; Religious n=31; Multiple n=12) were well-balanced on demographic and burial covariates (all p > 0.05) but differed significantly in exhumation delay (median 13, 27.5, 42, and 67 days respectively; p < 0.001). Global log-rank test confirmed significant between-group differences in time-to-exhumation (χ² = 26.41, df = 3, p < 0.001). Overall DNA success was 70.0% (84/120). Religious leader-mediated cases had significantly lower odds of DNA success in multivariable analysis (aOR 0.361, 95% CI 0.144–0.904, p = 0.030). Exhumation delay >30 days (OR 0.411, 95% CI 0.228–0.742, p = 0.003) and male gender (aOR 2.029, 95% CI 1.017–4.046, p = 0.045) were independently associated with DNA outcome. Conclusion: Sociocultural mediation type is a significant and independent predictor of both exhumation timeline and DNA extraction success in South Sumatran rural forensic casework. Religious leader-mediated cases incur a 29-day median delay compared with directly authorized cases, translating into measurable reductions in DNA yield. Formalisation of a Community Forensic Mediation Protocol at the provincial level is recommended.